Wind load interaction on an adjacent building - Peterka, J. A., author; Zambrano, Thomas Guy, author; Fluid Mechanics and Wind Engineering Program, Fluid Dynamics and Diffusion Laboratory, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1978)
In recent years, wind loading on buildings has been an area of active investigation by many authors. A review of this literature indicates that little information is available on the effect of an adjacent building on the pressure distribution mean force and moment coefficients and the probability density function of the peak pressures acting on a structure. Especially evident is the need for defining possible areas of augmented high wind loading. The purpose of this paper is to give a detailed picture of these effects for a set of upwind structures and relative positions. The results show where shielding and channeling effects can be of significant effect in mean-wind loading and local pressure distribution. Also, an attempt is made to predict local peak pressures resulting from building interaction using the statistical characteristics of wind.
CER77-78TGZ-JAP26.
March 1978.
Keywords: Wind-pressure; Buildings -- Aerodynamics